OBLIGATION TO MONITOR SERVICE USER TRANSACTIONS BY A NOTARY AS AN EFFORT TO PREVENT AND ERADICATE THE CRIME OF MONEY LAUNDERING - Nila Amalia; Syamsuddin Muchtar; Muhammad Ilham Arisaputra (Jurnal Ilmiah Advokasi, 2024)
Due to disharmony between Law on the Office of Notaries and Regulations of the Minister of Law and Human Rights Number 9 of 2017 in recognizing service users for notaries, in this case the lack of clarity regarding the regulation of service user transaction monitoring obligations so that notaries experience a dilemma in implementing Know Your Customer (KYC) and are more inclined to implement KYC according to Law on the Office of Notaries and Regulations of the Minister of Law and Human Rights Number 9 of 2017 considering Law on the Office of Notaries than the Notary Code of Ethics are the legal basis for a notary in carrying out his duties and authorities which in terms of the hierarchy of laws and regulations have a higher position than the Regulations of the Minister of Law and Human Rights Number 9 of 2017, this is in accordance with the principle of Lex Superior Derogate Legi Inferiori where higher regulations overrule lower regulations.Keywords: Transaction Monitoring, Notary, Money Laundering